How does iron-sulfur cluster coordination regulate the activity of human glutaredoxin 2? - Berndt, Carsten; Hudemann, Christoph; Hanschmann, Eva-Maria; Axelsson, Rebecca; Holmgren, Arne; Lillig, Christopher Horst (Antioxidants & redox signaling, 2007)
Human mitochondrial glutaredoxin (Grx2) was described as the first iron-sulfur protein from the thioredoxin superfamily of proteins. The [2Fe-2S] cluster was proposed to serve as redox sensor for the activation of Grx2 during oxidative stress. The authors have demonstrated that the iron-sulfur cluster is complexed by the two N-terminal active site thiols of two Grx2 monomers and two molecules of glutathione that are bound noncovalently to the proteins and in equilibrium with glutathione in solution. When reduced glutathione becomes the limiting factor for cluster coordination, the holo-Grx2 complex dissociates, yielding enzymatically active Grx2.